2017
DOI: 10.1080/20473869.2017.1335479
|View full text |Cite
|
Sign up to set email alerts
|

Salient employability skills for youth with intellectual and developmental disabilities in Singapore: the perspectives of job developers

Abstract: Objective: In order to increase employment opportunities for individuals with intellectual and developmental disabilities (IDDs), professionals are tasked with designing and implementing job training services to youth preparing to enter the job market. Having a better understanding of desirable employability skills aids in allowing professionals to develop programs that will target the needs of those who make decisions relating to human resources.Methods: This study features a qualitative research design to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Teamwork is the core to ensure the effective operation of the organization and all departments within the organization ( Watson et al, 2022 ) and is a highly sought-after competence by employers ( Parratt et al, 2016 ). A qualitative study on job developers revealed that soft skills such as communication and coordination were more desirable than job-related technical skills ( Scheef et al, 2019 ). Self-learning skill can keep individuals updated both in knowledge and competence to maintain competitiveness in the workplace and secure sustainable employment in the contemporary lifelong learning society ( Wang, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teamwork is the core to ensure the effective operation of the organization and all departments within the organization ( Watson et al, 2022 ) and is a highly sought-after competence by employers ( Parratt et al, 2016 ). A qualitative study on job developers revealed that soft skills such as communication and coordination were more desirable than job-related technical skills ( Scheef et al, 2019 ). Self-learning skill can keep individuals updated both in knowledge and competence to maintain competitiveness in the workplace and secure sustainable employment in the contemporary lifelong learning society ( Wang, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Employment is one of the primary goals of persons with intellectual disabilities (ID). Employment can lead to positive psychosocial and economic benefits for people with ID, including a sense of purpose, opportunities for new friendships, health, and better quality of life,[ 1 2 ] but people with disabilities are not afforded this opportunity to contribute to society through work[ 3 ] due to multiple barriers. Barriers such as difficulties in learning, stigmas, and lack of access to social environments are additional obstacles that predispose this section of the individuals to remain dependent on their families or government programs, with no real possibility of social and financial development field.…”
Section: Introductionmentioning
confidence: 99%